Oficina criativa: criatividade e sustentabilidade de um ideal - Burmann, Claudir (2009)
The last three decades of the past millennium represented profound changes for the Brazilian and Latin American societies. This assertive is also true in present times, with shifts in the capitalist system, with the introduction of new technologies and production techniques and management, altered intensely the relationships among people, at the work and family level, as well as in other areas and institutions of society. The migrations that occurred in Brazil towards urban areas and the North of country are part of the ongoing process of economic transformation. The migration towards the State of Rondônia, that started in the 70s, includes a copy of the economic policy developed in the country. The Evangelical Church of the Lutheran Confession (IECLB), in turn, saw the need to expand its presence beyond the Southern and Southeastern regions. A relevant number of migrants who went to North Brazil were members of the IECLB. In addition, in order to establish religious communities in so-called "New Settlement Areas", the IECLB cared about the technical assistance in the rural areas and assistance in the health area. Thus, several socio-diaconal projects of developmental nature were deployed. Other social/diaconal projects that emerged to posted in the area of ensuring individual and social rights. These projects fit into the context of the mobilization and struggle for social security over the decades of 1980 and 1990, with the fundamental reference of the new Constitution of 1988. The Project Oficina Criativa , later transformed into Beneficent Institution Oficina Criativa , linked to the Community Evangelical Lutheran Confession in Porto Velho, Rondônia, is in this whole context in terms of economy and politics, as well as being placed within the religious context of the churches in Brazilian and the IECLB. As a social/diaconal project, it has had the ability to reinvent itself, ensuring the sustainability of its ideal in the transformation of people's lives and society from the motivation of preaching and witness of Jesus Nazareth.